The Role of Principal Competencies in Enhancing Educational Quality at SMAN 1 Pacet Mojokerto - Herlina, Andi (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Educational quality improvement is a key priority influenced significantly by the principal’s role as an educational leader. Principals function not only as administrators but also as transformational leaders who drive synergistic efforts to achieve institutional goals. This study analyzes (1) the role of principal competencies in enhancing educational quality at SMAN 1 Pacet Mojokerto, and (2) the implications of these competencies. Using a descriptive qualitative method, data was collected through observation, interviews, and documentation involving the principal, deputy principal for curriculum, and educators. Data analysis employed the interactive model of Miles, Huberman, and Saldana, with verification conducted via source and technical triangulation. The findings reveal that the principal plays a strategic role in fostering a conducive learning environment, improving staff performance, and building a culture of excellence. (1) The principal’s role in quality enhancement is manifested through three interconnected competencies: Personality, Managerial, and Entrepreneurial. These roles directly impact the fulfillment of the National Education Standards concerning content, process, and graduate competence. (2) The implications are significant, leading to systematic curriculum implementation, directed innovation in program management, and maximized student potential.